Producing bright X-rays for imaging applications using a laser wakefield accelerator - Mangles, S; Bloom, MS; Bryant, J; Cole, J; Döpp, A; Kneip, S; Nakamura, H; Poder, K; Streeter, M; Wood, J; Najmudin, Z; Bendoyro, R; et al. (Optical Society of American (OSA), 2014)
We report on the generation of bright multi-keV betatron X-ray radiation using a GeV laser wakefield accelerator and investigate the use of these X-rays for various imaging applications. © 2014 Optical Society of America.